An Estimation of Crack Growth Life for the Tubes of Linear Part of the Oil Pipeline with the Longitudinal Semielliptical Crack after Long Time Operation - V.M. Veselukha (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2014)
To determine the crack growth resistance of tubes made of ductile steel using of approaches of linear elastic fracture mechanics it is incorrectly due to non-compliance with the conditions of plane strain. One of the variants of solutions to the problem lies in the extrapolation formulas for linear elastic fracture mechanics for stress intensity factor at a substantially nonlinear stage of deformation using functions amendments of the plasticity. The results of the cyclic crack growth resistance tests for samples made of tube steel on the basis of a new engineering-stock approach are given. The evaluation of crack growth life for tubes of linear part of the pipeline in the presence of dangerous longitudinal semi-elliptical crack at a given level of irregular operational loading and taking into account long-term (over 30 years) exposure to damaging factors are carried out.